Network Security Management and Protection using UTM Firewall - Solanki, Pratap Singh; P. R. , Khatarkar (International Journal of Computer Sciences and Engineering, 2019)
Information and Commutation Technology (ICT) is the most important strategic issue for any organization and in the age of digital industrialization, every establishment uses the ICT for running their business therefore they are more depended on network. Increasingly uses of ICT posing new security challenges. Network infrastructure is essential to enable the network for communication. All devices in network are equally important to run the network and in failure of any one device may have devastating effect on people, economy, government services and national security. In this hyper-connected world, protecting our network and data from unauthorized access are big challenge. Process of protecting network infrastructures and data from external destructive threats and intrusion is known as network security. Network security for every organization must be consider as essential for functioning of network system and must be dealt with proactive and timely manner. For the above said purposes it is essential to have a dedicated network security system which can perform security function viz. firewall, intrusion detection and prevention, antivirus etc. In this paper we are discussing about the implementation of Unified Threat Management (UTM) Firewall system for network security management and protecting the Network for CWPRS Local Area Network (CLAN). The UTM Firewall has been successfully implemented at CWPRS for indentifying and protecting the Network from internal and external threats.